India's food security resilience: some tips for ASEAN? - Montesclaros, Jose Ma. Luis P. (2022)
The IMF recently lauded India’s food subsidies in helping minimise COVID-19’s impacts on food and economic insecurity. What are the lessons for ASEAN member states, where extreme poverty increased by 4.7 million amid the pandemic?